A case report of papular variant of maculopapular cutaneous mastocytosis - Attasuriyanan, Manita; Kampirapap, Kowit (Thai Journal of Dermatology, 2017)
Although maculopapular cutaneous mastocytosis (MPCM) is the most common manifestation of cutaneous mastocytosis (CM), papular variant is quite rare. The subtype is clinically characterized by slightly tan or yellowish papules up to 1 cm in diameter. We report case of a 9-month old male infant presented with multiple discrete brownish papular lesions on the face, trunk and extremities. Darier’s sign was positive. The histopathology and special stainings were compatible with cutaneous mastocytosis. Complete physical examination revealed no hepatosplenomegaly. Laboratory investigations and pediatric dermatology consultation for further systemic involvements were performed. Although there was no evidence of systemic involvement at present, long term follow-up is recommended.